ANALISIS CIPTA KERJA MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2020 DAN FIQIH SIYASAH - Agus Susanto; Abdur Rahim (Jurnal Penelitian Multidisiplin Ilmu, 2022)
There are pros and cons to Law Number 11 of 2020 concerning job creation, where the regulation is not in accordance with the procedures for making laws and regulations and has not accommodated the needs of the wider community. So there fore the author wants to do research related to Job Creation Analysis according to Law Number 11 of 2020 and Fiqh Siyasah. The purpose of this study is to find out the results of the analysis of job creation according to Law Number 11 of 2020, and to understand the results of the analysis of job creation according to Fiqh Siyasah. This research is a type of library research, where the data sources are obtained from literature searches such as journal articles, internet sites, books, legal materials (laws), and other research results relevant to the topic of this research. The results of the analysis of job creation according to Law No. 11 of 2020 are Law No. 11 of 2020 regarding work creation, there are still many problems. Starting from the system for the formation of the laws and regulations as well as the articles that have been ratified, there are some that are ambiguous or unclear in their explanations, and also these regulations have not been studied in depth related to the needs of the wider community, as evidenced by the impartiality of these regulations to the entire community. While the results of the analysis of job creation according to Fiqh Siyasah are included in the category of Siyasah Duturiyah of Tasri'iyah power. The laws and regulations must have the principle of benefit for all people who are bound by these laws and regulations. And in its formation it must involve or be carried out by Ahlu Al-Halli wal Aqdi or the DPR with people from various groups or professions, because it is for the benefit of the people. Which in the formation of a Qonun or law must be carried out openly and involve elements of the community. This is done so that a Qonun is produced properly and also in accordance with the Qur'an and hadith.